Differences in the Influence of Driving Behavior on Pollution in Lombok Island - Suteja, I Wayan; Hasyim, Hasyim; Rohani, Rohani; Sideman, IAO Suwati; Mahendra, Made; Sanusi, Andi (Jurnal Biologi Tropis, 2024)
This study aims to analyze the effect of driving behavior on pollution on the island of Lombok. This study is a study with a Completely Randomized Design (CRD). Data collection was carried out by distributing questionnaires to respondents who met the criteria as respondents. This equation contains positive and negative statements that aim for respondents to read the statements carefully and answer with their own perceptions. The questionnaire in this study uses a Likert scale of 1-5 in measuring respondent perceptions. This study shows that driving behavior on Lombok Island has a significant influence on air pollution levels, especially in urban areas such as Mataram which have high traffic density. This pollution is caused by aggressive driving behavior, such as sudden acceleration and sudden braking, as well as low vehicle maintenance that increases exhaust emissions such as CO, NOx, and PM2.5. The impact not only reduces air quality and damages the ecosystem, but also increases cases of respiratory diseases such as ARI and asthma. Science-based solutions, such as the use of environmentally friendly vehicles, development of public transportation, and energy-efficient driving education, need to be implemented to reduce pollution and maintain environmental sustainability in Lombok.